Spread of vasodilatation and vasoconstriction along feed arteries and arterioles of hamster skeletal muscle - Segal, Steven S (Blackwell Science Inc, 1999)
1. In arterioles of the hamster cheek pouch, vasodilatation and vasoconstriction can spread via the conduction of electrical signals through gap junctions between cells that comprise the vessel wall. However, conduction in resistance networks supplying other tissues has received relatively little attention. In anaesthetized hamsters, we have investigated the spread of dilatation and constriction along feed arteries and arterioles of the retractor muscle, which is contiguous with the cheek pouch. 2. When released from a micropipette, acetylcholine (ACh) triggered vasodilatation that spread rapidly along feed arteries external to the muscle and arterioles within the muscle. Responses were independent of changes in wall shear rate, perivascular nerve activity, or release of nitric oxide, indicating cell-to-cell conduction. 3. Vasodilatation conducted without decrement along unbranched feed arteries, yet decayed markedly in arteriolar networks. Thus, branching of the conduction pathway dissipated the vasodilatation. 4. Noradrenaline (NA) or a depolarizing KCl stimulus evoked constriction of arterioles and feed arteries of the retractor muscle that was constrained to the vicinity of the micropipette. This behaviour contrasts sharply with the conduction of vasodilatation in these microvessels and with the conduction of vasoconstriction elicited by NA and KCl in cheek pouch arterioles. 5. Focal electrical stimulation produced constriction that spread rapidly along feed arteries and arterioles. These responses were inhibited by tetrodotoxin or prazosin, confirming the release of NA along perivascular sympathetic nerves, which are absent from arterioles studied in the cheek pouch. Thus, sympathetic nerve activity co-ordinated the contraction of smooth muscle cells as effectively as the conduction of vasodilatation co-ordinated their relaxation. 6. In the light of previous findings in the cheek pouch, the properties of vasoconstriction and vasodilatation in feed arteries and arterioles of the retractor muscle indicate that substantive differences can exist in the nature of signal transmission along microvessels of tissues that differ in structure and function.